Physico-chemical and biological properties of saccharides and alcohol after nuclear radiation treatment - V. T. Maslyuk; N. I. Svatiuk; N. V. Boyko; S. A. Burmey; O. I. Simkanych; O. O. Grabar; O. M. Pop; O. B. Tarnai; M. V. Goshovskyi; J. Y. Hainish (Ядерна фізика та енергетика)
The results of a complex study of the influence of nuclear radiation on the physical and chemical properties of distilled water, aqueous solutions of saccharides, ethyl alcohol, and their biological activity are presented. Irradiation was carried out on the M-30 microtron electron accelerator (12.5 MeV) and on isotope radiation stands based on 241Am, 137Cs, and 240Pu, which generate mixed nuclear radiation. The temporal evolution of chemical indicators and optical and frequency characteristics of electrical parameters of irradiated water environments are discussed. The selective biological effect of irradiated compounds on test microorganisms from different phylogenetic groups was established.